Incorporating Entrepreneurial Digital Storytelling in Teaching Business English - Muhammad Nasir (Universitas Brawijaya, 2024)
Entrepreneurship, as an academic discipline, in higher education institutions (HEIs) is crucial in supporting the government's mission to promote entrepreneurial education. As part of this trend, there have been growing interests in integrating entrepreneurship into a course’s curriculum, including in English as a Foreign Language (EFL) class, specifically within the Business English subject. This study proposes the incorporation of entrepreneurial digital storytelling (EDST) contents, encompassing personal narratives and real-life experiences of successful entrepreneurs within the Business English course in higher education settings. This study employs a qualitative approach through literature review to support the theoretical perspective and practical implementation of this study. The article highlights the benefits of incorporating entrepreneurial storytelling content to support EFL students in enhancing their motivation to learn English, particularly to improve the language skills. Furthermore, its implementation is useful for the development of students' entrepreneurial intentions and motivation while simultaneously enhancing their English language proficiency and academic growth.